Z-source inverter pulse width modulation: a survey - Mohd. Shafie, Bakar; N. A., Rahim; Kamarul Hawari, Ghazali; A. H. M., Hanafi (IEEE, 2011)
The paper presents switching techniques for pulse-width-modulated-based z-source inverter; simple boost PWM, maximum boost PWM, maximum constant boost PWM, modified-reference PWM, modified space vector PWM, hysteresis current control, and sine carrier PWM. Concepts and ideas behind the techniques are briefly explained. An overall view is summed up of the PWM controls, in terms of their achievements and system involvement in ZSI.